Cost Modelling For E-Learning Implementation In Higher Education With Fuzzy Activity Based Costing - Sholiq, Ach; Pribadi, Apol; Algadri, Ach Naser (Jurnal GEMATIKA, 2009)
This study presents a model of costing framework for the e-learning implementation by integrating the value chain, analysis, activity based costing, and fuzzy logic to Fuzzy Activity Based Costing (FABC). This method will be very useful in: (i) in the emerging economic era marked by rapid economic growth and global environmental uncertainty (ii) the limitations of historical accounting information. With the model can be known to the e-learning implementation costs per cost object that uses the e-learning, namely: (i) the cost per student, (ii) the cost per course, and (iii) the cost per Semester Credit System. The results obtained by the cost of implementation of e-learning in College XYZ per cost object is: (1) the cost per student of Rp 209,521.7 (2) The cost per course of Rp 8,333,250 (3) the cost per semester credit system of Rp 69.840.57. Research output is the estimation model of costing that can be used as a reference for noncollege or college institutions to conduct financial feasibility studies prior to implementing the e-learning